Analysis of Material Science and Techniques for Making Es Selendang Mayang - Destiani Rahmawati; Yudi Juniardi; Hidayatullah (Postgraduate, University of Mataram, 2025)
Es Selendang Mayang is a traditional drink from Betawi (Jakarta), Indonesia, popular for its sweet, savory flavor and colorful appearance (usually red, white, and green) resembling a scarf. The drink consists of three main components: a chewy cake called